Anti- Sporothrix spp. activity of medicinal plants - Stefanie Bressan Waller; Isabel Martins Madrid; Renata Osório de Faria; Marlete Brum Cleff; João Roberto Braga de Mello; Mário Carlos Araújo Meireles
ABSTRACT Cases of sporotrichosis in humans and animals without satisfactory clinical response have increased, a warning sign of strains resistant to conventional antifungal agents. The urgent search for alternative therapies was an incentive for research on medicinal plants with anti-Sporothrix spp. properties. A bibliographic survey was performed based on scientific papers about in vitro and in vivo antifungal activity of essential oils and extracts of plants in differents solvents against the fungal of the Sporothrix schenckii complex. The study methodology consisted of a literature review in Google Scholar, Science Direct, Pubmed, Bireme and Springer link with papers from 1986 to 2015. We found 141 species of plants that were investigated, of which 100 species were concentrated in 39 botanical families that had confirmed anti-Sporothrix activity. Combretaceae, Asteraceae and Lamiaceae represented the botanical families with the greatest number of plants species with antifungal potential, using different methodologies. However, there are few studies with medicinal plants in experimental infection in animals that prove their activity in the treatment of sporotrichosis. It reinforces the need for further research related to standardization of in vitro methodologies and in vivo studies related to safety and to toxicity potential of these plants with anti-Sporothrix spp. activity.